2012
DOI: 10.1016/j.ijgo.2011.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cervical intraepithelial neoplasia in a cohort of HIV‐infected women

Abstract: The CIN incidence was low despite the high HPV prevalence. Being younger than 19 years at first sexual intercourse and not using antiretroviral medications were found to be the main risk factors for CIN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
3
9
0
Order By: Relevance
“…High HPV infection prevalence in HIV-positive women has been reported in worldwide studies; there is 44% HPV infection in European countries such as Italy [5] and US studies have found 54%-73% prevalence [20,21], similar to that for Latin-American countries like Brazil where 48% to 68% HPV prevalence has been found in HIV-positive women [22,23]. …”
Section: Discussionmentioning
confidence: 85%
“…High HPV infection prevalence in HIV-positive women has been reported in worldwide studies; there is 44% HPV infection in European countries such as Italy [5] and US studies have found 54%-73% prevalence [20,21], similar to that for Latin-American countries like Brazil where 48% to 68% HPV prevalence has been found in HIV-positive women [22,23]. …”
Section: Discussionmentioning
confidence: 85%
“…In a retrospective cohort study, Araujo et al (2012) showed HPV in 68.1% of HIV+ women, of which, 17.2% had HR-HPV, 12.9% had LR-HPV, and HR-and LR-HPV co-infections accounted for 23.6%. In this study, HPV was not genotyped in 14,4% of women.…”
Section: Molecular Prevalence Of Hpv and Genotypes In Hiv+ Women Accomentioning
confidence: 99%
“…This increased risk for cervical cancer has led to increased follow-up and closer screening recommendations. 11,12 Most of these data came before antiretroviral medications were consistently in use 4,13 and data in the combined antiretroviral therapy (cART) era are just emerging, 14 particularly around progression and regression.…”
mentioning
confidence: 99%